2016
DOI: 10.1080/21513732.2016.1193560
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oil palm expansion through direct and indirect land use change in Tapi river basin, Thailand

Abstract: The Thai government has ambitious plan to further promote the use of biodiesel. However, there has been insufficient consideration on the environmental effects of oil palm expansion in Thailand. This paper focuses on the effects of oil palm expansion on land use. We analysed the direct land use change (dLUC) and indirect land use change (iLUC) caused by the oil palm expansion and its effects on ecosystem services supply. Our analysis shows that between 2000 and 2009 dLUC related to oil palm expansion was more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…While understanding the likely linkage between decreased ES and oil palm development around them, local communities still like growing such a lucrative crop. Aware of the dilemma, they still favor palm oil development mostly because of the benefits of high revenue (Feintrenie et al, 2010;Pfund et al, 2011;Saswattecha et al, 2016), yet losses from forest income, other crops, and fish might be higher than previously assumed (Angelsen et al, 2014). We found that local communities motivated by several reasons other than the economy for planting palm, such as unpredictable weather, governmental policies, government incentives (Rist et al, 2010), as well as influencing from neighbors ( Figure 5).…”
Section: Reasons For Growing Oil Palmmentioning
confidence: 80%
See 1 more Smart Citation
“…While understanding the likely linkage between decreased ES and oil palm development around them, local communities still like growing such a lucrative crop. Aware of the dilemma, they still favor palm oil development mostly because of the benefits of high revenue (Feintrenie et al, 2010;Pfund et al, 2011;Saswattecha et al, 2016), yet losses from forest income, other crops, and fish might be higher than previously assumed (Angelsen et al, 2014). We found that local communities motivated by several reasons other than the economy for planting palm, such as unpredictable weather, governmental policies, government incentives (Rist et al, 2010), as well as influencing from neighbors ( Figure 5).…”
Section: Reasons For Growing Oil Palmmentioning
confidence: 80%
“…Despite this, our results showed that many villagers from the four communities expressed interest in developing their own oil palm plantations not only one, but because of several reasons, in view of the income (Feintrenie et al, 2010;Rist et al, 2010;Pfund et al, 2011;Sayer et al, 2012) and other benefits that oil palm offers. These benefits include being highly tolerant to natural hazards, avoiding the pests that affected rice (Rist et al, 2010;Saswattecha et al, 2016), withstanding unpredictable weather events (Masato Kawanishi, 2013), and government policies (Rist et al, 2010). The loss of traditional forms of employment can be offset by new employment opportunities in the oil palm sector; this change in livelihoods can affect the relationship that people have with their natural resources and services which underpins their cultural identities.…”
Section: Discussion Common Agreed Upon Es To Manage the Oil Palm Lanmentioning
confidence: 99%
“…But along with the land use change that occurred, the area of wetland rice has declined. In addition there are some losses that must be calculated as a negative impact of the function of rice fields, such as the loss of potential rice production, loss of employment opportunities, and the increasingly damaged environment (Saswattcha et al 2016). Based on previous studies, in this study it is suspected that there are factors that influence the decision of farmers to transfer land functions.…”
Section: Review Of Literaturementioning
confidence: 92%
“…While excluding environmental indicators, a recent CGE study of Thai biofuel production also provided suggestive evidence on how future biofuel expansion may lead to increased demand for palm oil and land use for oil palm production (Wianwiwat and Asafu-Adjaye, 2013). Other Thai-specific environmental studies of oil palm and palm oil production include more detailed LUC studies of oil palm production (Saswattecha et al, 2016), as well as partial life-cycle (Saswattecha et al, 2015) and full life-cycle (Silalertruksa et al, 2017) LUC- and process-oriented studies. While the latter studies provide a variety of environmental and ecological indicators which we do not include in our study, e.g.…”
Section: Background Literaturementioning
confidence: 99%